Molecular detection and identification of Begomovirus infecting cucumber (Cucumis sativus) in Terengganu, Malaysia - Sakthivel Poraya Goundar; Sandhya Ramani; Nuramirashafikah Mohd Radzi; Mohd Fahmi Abu Bakar; Hasan Nudin Nur Fatihah (Penerbit Universiti Kebangsaan Malaysia, 2024)
The genus Begomovirus from the family Geminiviridae is responsible for causing significant economic losses to many important horticultural crops, including cucumber (Cucumis sativus L.). Begomovirus infection during the early stages of plant growth can lead to complete yield loss. Hence, the identification of begomovirus species is important to design a precise resistant breeding strategy. This study aims to detect the presence of begomovirus in typical symptomatic cucumber leaves, identify the species of begomovirus present, and investigate the evolutionary relationships with other reported begomoviruses using phylogenetic analysis. Leaf samples from symptomatic cucumber plants were collected from the Green World Genetics (GWG) research station and a farm in Lembah Bidong, Rhu Tapai, Setiu, Terengganu. To detect the presence of begomovirus, PCR was carried out using universal primers targeting DNA-A, DNA-B, and betasatellite regions. DNA-A and betasatellite fragments were amplified, but not DNA-B. The amplified partial sequences of DNA-A were then analysed and compared with other begomovirus sequences in the GenBank database managed by the National Centre for Biotechnology Information (NCBI). The newly isolated DNA-A sequence from cucumber was 100% identical to the tomato leaf curl New Delhi virus (ToLCNDV). The phylogenetic tree was divided into two groups: group A, consisting of the newly isolated DNA-A sequence from cucumber, ToLCNDV, followed by squash leaf curl China virus (SLCCNV) and a monopartite begomovirus Ageratum yellow vein virus (AYVV); and group B, consisting of tomato yellow leaf curl Kanchanaburi virus (TYLCKaV), pepper yellow leaf curl Indonesia virus (PepYLCIV), and pepper yellow leaf curl Aceh virus (PepYLCAV). For the first time in cucumber, betasatellite is reported in association with ToLCNDV, a bipartite old-world begomovirus. This study provides a basis for the selection and breeding of begomovirusresistant cucumber varieties in the future.